Sacred Space in the Cap Sac Ritual of the Dao Lan Ten People in Vietnam - PhD. Tran Huu Son; PhD. Dang Thi Oanh; MSc. Bach Kim Chi (RA Journal Of Applied Research, 2024)
In rituals, especially religious rituals, sacred space plays an important role. Sacred space regulates ritual functions while also reflecting ritual values.